Navigating environmental, economic, and technological trade-offs in the design and operation of submerged anaerobic membrane bioreactors (AnMBRs). (15th December 2015) - Pretel, R.; Shoener, B.D.; Ferrer, J.; Guest, J.S.
Abstract: Anaerobic membrane bioreactors (AnMBRs) enable energy recovery from wastewater while simultaneously achieving high levels of treatment. The objective of this study was to elucidate how detailed design and operational decisions of submerged AnMBRs influence the technological, environmental, and economic sustainability of the system across its life cycle. Specific design and operational decisions evaluated included: solids retention time ( SRT ), mixed liquor suspended solids ( MLSS ) concentration, sludge recycling ratio ( r ), flux ( J ), and specific gas demand per membrane area ( SGD ). The possibility of methane recovery (both as biogas and as soluble methane in reactor effluent) and bioenergy production, nutrient recovery, and final destination of the sludge (land application, landfill, or incineration) were also evaluated. The implications of these design and operational decisions were characterized by leveraging a quantitative sustainable design (QSD) framework which integrated steady-state performance modeling across seasonal temperatures (using pilot-scale experimental data and the simulating software DESASS), life cycle cost (LCC) analysis, and life cycle assessment (LCA). Sensitivity and uncertainty analyses were used to characterize the relative importance of individual design decisions, and to navigate trade-offs across environmental, economic, and technological criteria. Based on this analysis, there are design and operational conditions under which submerged AnMBRs could be net energy positive and contribute to the pursuit of carbon negative wastewater treatment. Graphical abstract: Highlights: A quantitative sustainable design for submerged AnMBR is proposed in this study. Design and operational decisions were evaluated for impacts on sustainability. Flux, gas sparging, and suspended solids resulted in sustainability trade-offs. Suspended solids and flux had the greatest influence in environmental/economic terms. Energy positive treatment can be achieved at higher operating temperatures.